Comparative Politics of Welfare in the Special Region of Yogyakarta and Central Java: A Case Study of the BPJS Ketenagakerjaan Program in 2023: Perbandingan Politik Kesejahteraan di Provinsi DIY dan Jawa Tengah, Studi Kasus Program BPJS Ketenagakerjaan Tahun 2023 - Thomas Rizki Ali; Luthfi Makhasin (Universitas Indo Global Mandiri, 2026)
Purpose : This study aims to analyze the participation of informal workers in the BPJS Employment program in Indonesia, particularly in the Provinces of Central Java and the Special Region of Yogyakarta, and to examine the differences in policy implementation using the power resource approach developed by Walter Korpi. Design/methodology/approach : This research employs a literature review and data collection methods to analyze the implementation of social security programs for informal workers in Central Java and the Special Region of Yogyakarta in 2023. Findings : The findings show that the participation rate in Yogyakarta reached nearly 37% of the total labor force, while in Central Java it was only around 24%, indicating differences in the effectiveness of policy implementation between the two regions. Local government policies and budget support play a crucial role in increasing participation among informal workers, while economic constraints, low levels of education, and lack of socialization reflect weak power resources, which hinder workers from accessing social security programs. Practical Implication : The findings highlight the importance of strong local government commitment, budget support, and targeted socialization to increase informal workers’ participation in social security programs. Originality/value : This study provides a novel perspective by applying the power resource approach of Walter Korpi at the subnational level, showing that participation differences are influenced not only by economic factors but also by political commitment and distribution of power. Paper type : Research Paper